Nurse caring behavior and satisfaction of inpatient patients on nursing services - Tutu April Ariani; Nur Aini (University of Muhammadiyah Malang, 2018)
Nurses are at the forefront of health care. Satisfied or not the patient to the health service is an indicator and one of the determinants of good quality of nursing service quality. Professional and qualified nurses must have hard skill and soft skill skills. Soft skill skills include the ability to communicate, empathy and caring. Caring is an attitude of caring, respect and respect for others. In fact, many nurses do not reflect caring behavior in giving nursing care to clients. The purpose of this study is to provide intervention in the form of therapeutic communication to develop or improve caring behavior of nurses so that this will affect the quality of nursing service & patient satisfaction. Type of research is pre experiment. Sample of six nurses were taken with sampling quota technique and patient of five people taken by purposive sampling technique. The research was conducted at Rumkit Tk II. Dr. Soepraoen Malang. The research variables were caring and patient satisfaction. Intervention given is therapeutic communication training for 1 month. Data analysis using univariate analysis. There is an increase in caring behavior of nurses, especially in terpeutik communication and increased patient satisfaction after nursing care given by nurses who have received caring behavior training: It is recommended to the nurse to maintain caring behavior in every nursing care in patients, especially in communicating.